Cross-cultural adaptation and psychometric properties of the Malay version of parenting and child tooth brushing assessment (M-PACTA) - Yu Jie Chin; Shani Ann Mani; Jennifer Geraldine Doss; Sabri Musa; Mahmoud Danaee (BMC, 2024)
Abstract Background Malaysian preschool children continue to exhibit a high prevalence of dental caries and poor oral hygiene. There is a need to gain an in-depth understanding of oral hygiene habits and design suitable interventions to improve oral hygiene in early childhood. Objective To cross-culturally adapt and determine the psychometric properties of the Malay-translated Parenting and Child Tooth Brushing Assessment questionnaire (M-PACTA). Methodology This cross-sectional study involved face and content validation, and forward and back-translation of PACTA. The M-PACTA was then tested for reliability and construct validity on 150 Malaysian parents of children aged 5 to 6 years old. Results Face validity indicated that the M-PACTA items were clear and easy to understand. For content validity, some words had to be modified in accordance with the recommendations of the expert committees to make it more coherent to Malaysians. Some statements in the parental knowledge scales were modified according to the guidelines applicable in Malaysia. The content comparison of the back translation with the adapted PACTA revealed that all items were semantic and linguistically equivalent. Exploratory factor analyses of M-PACTA suggested a two-factor structure for three scales including child behaviour scale ('non-compliance' and 'avoidance behaviour'), parental attitudes ('lack of concern' and 'attitude of care'), and parental knowledge ('general tooth brushing knowledge' and 'awareness of tooth brushing care') while for the parental strategy scale, three-factor structure was extracted including 'routine positive methods', 'uncommon positive methods', and 'negative methods'. Internal consistencies for all scales were good (α > 0.9). Conclusion M-PACTA did not replicate the construct of the original PACTA. Nonetheless, M-PACTA demonstrated good construct validity, internal consistency reliability, and test-retest reliability within Malaysian context.